Using Blur for Perceptual Investigation and Training in Sport? A Clear Picture of the Evidence and Implications for Future Research - Limballe, Annabelle; Kulpa, Richard; Bennett, Simon (Frontiers in Psychology, 2022)
Perceptual-cognitive skills are determinant in elite sport performance. Interactive sports required athletes to identify, pick-up and process the useful information in a very limited time, to make the best action choice. Recently, sport scientists investigated ways to assess and train perceptual-cognitive skills. Among those methods, the use of blur was developed. However, more understanding of the mechanisms involved are needed. Gaussian blur is particularly suited to design studies investigating perceptual skills in sport to produce the visual stimuli. Thus, we define in this paper the different type of blur (dioptric and Gaussian). Then we reviewed the current knowledge of the effect of blur in sport context. The use of blur is promising for development of novice skills, especially with the use of a peripheral blur. However, the current results are more cautious about benefit on experts’ performance. Finally, the previous experiments raised issues, especially with a 2D screen display. Virtual reality could be a way to develop the research on blur in sport context.